Analysis of Reward and Punishment in EFL Classroom - Syarifuddin, Sri Wahyuni; Zulfah, Zulfah (Al-Iftah: Journal of Islamic studies and society, 2021)
Classroom management is certainly concerned with behavior to create and maintain an effective learning experience. Therefore, giving rewards and punishments is important in order to increase students’ motivation in EFL classroom. The purpose of this study is to analyze (i) teachers’ perception (ii) teachers’ performance in using reward and punishment, (iii) to find out the kinds of reward and punishment used by the teachers and (iv) to know merit and demerit of reward and punishment.This study employed qualitative research method. The subjects of this research are 5 teachers from Elementary School, 5 teachers of Junior high school and 5 teachers of Senior High School in Parepare. The data were collected through interviews. Then the data was processed based on data reduction techniques, data presentation, and drawing conclusion. The findings showed that (i) reward and punishment is very useful for the teacher in managing the classroom, (ii) the teachers faced some problems in using reward and punishment such as, inconsistent, unfair and make other students jealous. (ii) theteachers used two kinds of reward; instructional reward (exam exemption, task exemption and early break) and non-instructional reward (praise, physical contact, and token reward) and two kinds of punishment; instructional punishment (punishment by action) and non-instructional punishment. (grade, penalty and punishment by words). Therefore, it can be concluded that the types of rewards and punishments that mostly used by teachers are praise and penalty punishment. So reward is good strategy to improve students’ motivation and punishment could make the students disciplined.